Kedudukan Fatwa Majelis Ulama Indonesia (MUI) dan Fatwa Dewan Syariah Nasional (DSN) Dalam Sistem Hukum Indonesia - Badrut Tamam, Ahmad (Al-Musthofa: Journal of Sharia Economics, 2021)
Referring to Law Number 12 of 2011 concerning the Establishment of Legislation, the MUI Fatwa is not a type of legislation that has binding legal force. The DSN-MUI fatwa and the MUI fatwa are both not included in the hierarchy of laws and regulations in Indonesia, but the fatwa issued by the National Sharia Council of the Indonesian Ulama Council (DSN-MUI) is a positive law that is binding. Because, its existence is often legitimized through laws and regulations by government institutions, so sharia economic actors must obey.